2005
DOI: 10.1097/01.pec.0000150988.26852.a6
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Associated With Alcohol Ingestion in Adolescence

Abstract: An alcohol-naive 16-year-old male is presented with alcohol-induced atrial fibrillation. Past medical history, review of systems, and presentation were all otherwise benign. Atrial fibrillation occurred early in the intoxication at an alcohol level slightly higher than the legal limit for intoxication (153 mg/dL). His complete cardiac evaluation was otherwise normal. The atrial fibrillation was not treated aggressively and resolved as the alcohol level quickly fell to zero, consistent with his "nonalcoholic" m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
(6 reference statements)
0
3
0
1
Order By: Relevance
“…In this view, the prognostic impact of potentially recurrent LV dysfunction secondary to habitual light alcohol drinking is worthy of further exploration. An association between ethanol intake and acute rhythm disturbances including atrial fibrillation and life‐threatening ventricular arrhythmias—the so‐called holiday heart syndrome (Koul et al., 2005)—has been described after binge drinking in individuals with no clinical evidence of heart disease (Thornton, 1984). Nonetheless, whether an acute depression in LV myocardial function may play a role in the genesis of this syndrome is unknown (Cameli et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In this view, the prognostic impact of potentially recurrent LV dysfunction secondary to habitual light alcohol drinking is worthy of further exploration. An association between ethanol intake and acute rhythm disturbances including atrial fibrillation and life‐threatening ventricular arrhythmias—the so‐called holiday heart syndrome (Koul et al., 2005)—has been described after binge drinking in individuals with no clinical evidence of heart disease (Thornton, 1984). Nonetheless, whether an acute depression in LV myocardial function may play a role in the genesis of this syndrome is unknown (Cameli et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…binge drinking), which could increase the risk of triggering a single episode of atrial fibrillation, as reported anecdotally. [32][33][34][35][36]…”
Section: Plausible Explanationsmentioning
confidence: 99%
“…After four weeks of abstinence, the test was repeated and no atrial fibrillation was observed. Finally, Koul et al (2005) described one case of alcohol-induced atrial fibrillation in a 16-year-old male.…”
Section: Alcohol and Cardiac Arrhythmiasmentioning
confidence: 99%